Low-Dose vs Standard-Dose Alteplase in Acute Lacunar Ischemic Stroke: The ENCHANTED Trial. (16th March 2021) - Zhou, Zien; Delcourt, Candice; Xia, Chao; Yoshimura, Sohei; Carcel, Cheryl; Torii-Yoshimura, Takako; You, Shoujiang; Malavera, Alejandra; Chen, Xiaoying; Hackett, Maree L.; Woodward, Mark; Chalmers, John; et al.
Abstract : Objective: To determine any differential efficacy and safety of low- vs standard-dose IV alteplase for lacunar vs nonlacunar acute ischemic stroke (AIS), we performed post hoc analyzes from the Enhanced Control of Hypertension and Thrombolysis Stroke Study (ENCHANTED) alteplase dose arm. Methods: In a cohort of 3, 297 ENCHANTED participants, we identified those with lacunar or nonlacunar AIS with different levels of confidence (definite/according to prespecified definitions based on clinical and adjudicated imaging findings. Logistic regression models were used to determine associations of lacunar AIS with 90-day outcomes (primary, modified Rankin Scale [mRS] scores 2–6; secondary, other mRS scores, intracerebral hemorrhage [ICH], and early neurologic deterioration or death) and treatment effects of low- vs standard-dose alteplase across lacunar and nonlacunar AIS with adjustment for baseline covariables. Results: Of 2, 588 participants with available imaging and clinical data, we classified cases as definite/probable lacunar (n = 490) or nonlacunar AIS (n = 2, 098) for primary analyses. Regardless of alteplase dose received, lacunar AIS participants had favorable functional (mRS 2–6, adjusted odds ratio [95% confidence interval] 0.60 [0.47–0.77]) and other clinical or safety outcomes compared to participants with nonlacunar AIS. Low-dose alteplase (versus standard) had no differential effect on functional outcomes (mRS 2–6, 1.04 [0.87–1.24]) but reduced the risk of symptomatic ICH in all included participants. There were no differential treatment effects of low- vs standard-dose alteplase on all outcomes across lacunar and nonlacunar AIS (all p interaction ≥0.07). Conclusions: We found no evidence from the ENCHANTED trial that low-dose alteplase had any advantages over standard dose for definite/probable lacunar AIS. Classification of Evidence: This study provides Class II evidence that for patients with lacunar AIS, low-dose alteplase had no additional benefit or safety over standard-dose alteplase. Clinical Trial Registration: Clinicaltrials.gov identifier NCT01422616.